Different Effects of Intramedullary Injection of Mesenchymal Stem Cells During the Acute vs. Chronic Inflammatory Phase on Bone Healing in the Murine Continuous Polyethylene Particle Infusion Model - Utsunomiya, Takeshi; Zhang, Ning; Lin, Tzuhua; Kohno, Yusuke; Ueno, Masaya; Maruyama, Masahiro; Rhee, Claire; Huang, Ejun; Yao, Zhenyu; Goodman, Stuart B. (Frontiers in Cell and Developmental Biology, 2021)
Chronic inflammation is a common feature in many diseases of different organ systems, including bone. However, there are few interventions to mitigate chronic inflammation and preserve host tissue. Previous in vitro studies demonstrated that preconditioning of mesenchymal stem cells (pMSCs) using lipopolysaccharide and tumor necrosis factor-α polarized macrophages from a pro-inflammatory to an anti-inflammatory phenotype and increased osteogenesis compared to unaltered MSCs. In the current study, we investigated the local injection of MSCs or pMSCs during the acute versus chronic inflammatory phase in a murine model of inflammation of bone: the continuous femoral intramedullary polyethylene particle infusion model. Chronic inflammation due to contaminated polyethylene particles decreased bone mineral density and increased osteoclast-like cells positively stained with leukocyte tartrate resistant acid phosphatase (TRAP) staining, and resulted in a sustained M1 pro-inflammatory macrophage phenotype and a decreased M2 anti-inflammatory phenotype. Local injection of MSCs or pMSCs during the chronic inflammatory phase reversed these findings. Conversely, immediate local injection of pMSCs during the acute inflammatory phase impaired bone healing, probably by mitigating the mandatory acute inflammatory reaction. These results suggest that the timing of interventions to facilitate bone healing by modulating inflammation is critical to the outcome. Interventions to facilitate bone healing by modulating acute inflammation should be prudently applied, as this phase of bone healing is temporally sensitive. Alternatively, local injection of MSCs or pMSCs during the chronic inflammatory phase may be a potential intervention to mitigate the adverse effects of contaminated particles on bone.